Integration of plasmonic heating and on‐chip temperature sensor for nucleic acid amplification assays. Issue 7 (23rd March 2020) - Monshat, Hosein; Wu, Zuowei; Pang, Jinji; Zhang, Qijing; Lu, Meng
Abstract: Nucleic acid tests have been widely used for diagnosis of diseases by detecting the relevant genetic markers that are usually amplified using polymerase chain reaction (PCR). This work reports the use of a plasmonic device as an efficient and low‐cost PCR thermocycler to facilitate nucleic acid‐based diagnosis. The thermoplasmonic device, consisting of a one‐dimensional metal grating, exploited the strong light absorption of plasmonic resonance modes to heat up PCR reagents using a near‐infrared laser source. The plasmonic device also integrated a thin‐film thermocouple on the metal grating to monitor the sample temperature. The plasmonic thermocycler is capable of performing a PCR amplification cycle in ~2.5 minutes. We successfully demonstrated the multiplex and real‐time PCR amplifications of the antibiotic resistance genes using the genomic DNAs extracted from Acinetobacter baumannii, Klebsiella pneumonia, Escherichia coli and Campylobacter . Abstract : We report a novel plasmonic thermocycler, which integrates a plasmonic heater and thermocouple on a plastic substrate. Taking advantage of the plasmonic resonance effect, the device can efficiently absorb light in near‐infrared, turn the absorbed energy into heat and drive the polymerase chain reaction. Meanwhile, the on‐chip thermocouple can monitor the reagent temperature. The sub‐wavelength plasmonic structure was fabricated inexpensively using nanoimprint lithography followed by evaporations of thin‐film stack.